2003
DOI: 10.1002/food.200390000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of menadione (vitamin K3) addition on lipid oxidation and tocopherol content in plant oils

Abstract: The effect of added menadione (vitamin K3) on stored corn and wheat germ oil on the dissolution and dimerization of natural tocopherols and autoxidation of triacylglycerols was investigated. Samples of corn and wheat germ oils pure and with added menadione were stored at +20 degrees C in brown and transparent glass bottles. During storage their peroxide value, changes of the content of fatty acids and dissolution of tocopherols were measured. Destruction of individual tocopherols in tested oils with menadione … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…(10700 ppm), magnesium (82950 ppm) and calcium (268 ppm), sodium (242 ppm), manganese (236 ppm) while zinc (158 ppm), iron (88 ppm) and copper (10 ppm) were in minor amount. In another study, the mineral content of wheat germ were found to be potassium (1087.39 ppm), magnesium (220.57 ppm), calcium (44.59 ppm), manganese (17.21 ppm), zinc (16.89 ppm), sodium (10.56 ppm), iron (10.19 ppm) and copper (1.02 ppm) content were much lower than that of our samples (Kupczyk and Gogolewski, 2003). Although, several factors may affect the elemental contents of plants such as the variety, harvesting time, soil type, soil conditions, fertilization, irrigation and weather etc (Ahmet and Bouhadjera, 2010;Kan et al, 2005).…”
Section: The Mineral Composition Of Wheat Germcontrasting
confidence: 69%
See 1 more Smart Citation
“…(10700 ppm), magnesium (82950 ppm) and calcium (268 ppm), sodium (242 ppm), manganese (236 ppm) while zinc (158 ppm), iron (88 ppm) and copper (10 ppm) were in minor amount. In another study, the mineral content of wheat germ were found to be potassium (1087.39 ppm), magnesium (220.57 ppm), calcium (44.59 ppm), manganese (17.21 ppm), zinc (16.89 ppm), sodium (10.56 ppm), iron (10.19 ppm) and copper (1.02 ppm) content were much lower than that of our samples (Kupczyk and Gogolewski, 2003). Although, several factors may affect the elemental contents of plants such as the variety, harvesting time, soil type, soil conditions, fertilization, irrigation and weather etc (Ahmet and Bouhadjera, 2010;Kan et al, 2005).…”
Section: The Mineral Composition Of Wheat Germcontrasting
confidence: 69%
“…Vitamin E compounds (tocopherols and tocotrienols) are effective inhibitors of lipid oxidation in food and biological systems. Tocopherols are a very important dietary nutrient for human and animals because they are only synthesized by plants (Kupczyk and Gogolewski, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The phytosteryl ferulate esters of rice bran oil, g-oryzanols, are important antioxidants in this oil [74]. Other lipid-soluble compounds, such as menadione (vitamin K3), are also found to exert protective effects against lipid oxidation and tocopherol degradation in vegetable oils [75]. The effects of natural antioxidants, such as phenolic acids, lignans, lecithins, and oryzanols on the stability of frying oils have already been discussed [76].…”
Section: Interaction Between Tocopherols and Other Components Of Vegementioning
confidence: 99%
“…K3) on the dissolution and dimerization of natural tocopherols in rapeseed and soybean oils and autoxidation of triacylglycerols. Menadione, with its chemical structure like a p-benzoquinone (mild oxidant generally used for the oxidation of tocopherols), can cause dissolution and dimerization of tocopherols [7,15]. Plant oils are added to The effect of added menadione (vit.…”
Section: Introductionmentioning
confidence: 99%